Islamic Microfinance Model: Civil Legal Features and Mechanisms (International Journal of Scientific Trends, 2026)
Islamic microfinance has expanded beyond a niche ethical alternative and is increasingly framed as a legally engineered instrument of financial inclusion. Yet the legal architecture that makes Islamic microfinance enforceable in secular jurisdictions – while remaining Shariah-compliant – remains conceptually under-theorised in comparative legal scholarship. This paper develops a legal typology of Islamic microfinance mechanisms and evaluates their institutional feasibility across regulatory regimes, with implications for emerging jurisdictions in Central Asia, including Uzbekistan. The study applies doctrinal legal analysis, comparative law across three jurisdictions (Malaysia, Indonesia, GCC – illustrated by UAE, Saudi Arabia practice), and institutional (regulatory) framework analysis. Elements of law & economics are used to assess transaction costs, incentive alignment, and enforcement risks. The paper offers a typology of Islamic microfinance contracts (murabaha, musharaka, mudaraba, ijara, salam, istisna, qard hasan, microtakaful) as legal forms of risk allocation; a governance-and-compliance matrix showing how Shariah governance (Shariah boards, audits, disclosure) functions as a hybrid of private ordering and public oversight; and a comparative table linking each mechanism to enforceability constraints, consumer protection tools, and regulatory arbitrage risks. Policy recommendations address licensing, disclosure of “price” (profit rate vs fees), responsible financing, Shariah governance accountability, AML (CFT), data protection, and dispute resolution design for scalable Islamic microfinance.